2021
DOI: 10.3390/jpm11111140
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex on the Genetic Susceptibility to Childhood Asthma in Latinos and African Americans

Abstract: Asthma is a respiratory disease whose prevalence changes throughout the lifespan and differs by sex, being more prevalent in males during childhood and in females after puberty. In this study, we assessed the influence of sex on the genetic susceptibility to childhood asthma in admixed populations. Sex-interaction and sex-stratified genome-wide association studies (GWAS) were performed in 4291 Latinos and 1730 African Americans separately, and results were meta-analyzed. Genome-wide (p ≤ 9.35 × 10−8) and sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In previous studies, male and female-specific genetic markers have been associated with asthma. 22 , 25 However, these studies did not consider the influence of socio-demographic, socio-economic, and lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, male and female-specific genetic markers have been associated with asthma. 22 , 25 However, these studies did not consider the influence of socio-demographic, socio-economic, and lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Studies have shown that several gene polymorphisms and gene expressions associated with asthma are sex-specific. [22][23][24][25] For instance, a large genome-wide association study (GWAS) using EVE Asthma Genetics Consortium discovered six sex-specific asthma risk loci, with two male-specific SNPs in/near IRF and RAB11FIP2 gene and four female-specific SNPs in/near RAP1GAP2, C6orf118, ERBB4, and AK057517. 25 Other sex-specific polymorphisms in many genes have been identified, eg, a male-specific SNP in the LCORL gene was significantly associated with childhood asthma, 22 and a female-specific polymorphism in the COX-2 −765 gene was significantly associated with bronchial asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focused on sex differences in asthma after adolescence identified that changes in DNA methylation in blood and lung tissue could play a role in the observed disparities ( 171 178 ). Furthermore, the interaction between sex-specific and sex-stratified genomes has also been found associated with childhood asthma ( 179 ). In this regard, the 17q12-21 -asthma locus was highlighted to be associated with asthma in both males and females but was widely significant in females ( 179 ).…”
Section: Influence Of the Genetic Framework In Sex Differences In Air...mentioning
confidence: 99%
“…Furthermore, the interaction between sex-specific and sex-stratified genomes has also been found associated with childhood asthma ( 179 ). In this regard, the 17q12-21 -asthma locus was highlighted to be associated with asthma in both males and females but was widely significant in females ( 179 ). Similarly, the ligand-dependent nuclear receptor co-repressor-like gene, located within the regulatory region was highlighted in males only ( 179 ).…”
Section: Influence Of the Genetic Framework In Sex Differences In Air...mentioning
confidence: 99%
See 1 more Smart Citation